Numerical analysis of compliance and fatigue life of the CCC specimen. (May 2023) - Neto, D.M.; Antunes, F.V.; Sérgio, E.R.; Branco, R.; Camacho-Reyes, A.; Diaz, F.; Gómez Gonzales, G.L.; Vasco-Olmo, J.
Highlights: The CCC specimen is a cylindrical specimen with central crack, produced by additive manufacturing. The compliance increases non-linearly with crack radius; the variation is small for the shorter cracks. An expression was proposed for the compliance, useful for the future experimental measurement of crack length. Fatigue life is predicted numerically using an approach based on cumulative plastic strain. Abstract: This study presents the numerical evaluation of the compliance in the CCC specimen aiming to assess the crack length inside the specimen. The numerical model considered the elastoplastic behaviour of the specimen, which is modelled using axisymmetric finite elements. The results shown that the propagation of the crack yields a non-linear increase of the compliance. Nevertheless, variation of the compliance is very small for small values of crack radius. Considering a loading sequence composed by four load blocks of constant amplitude, the fatigue crack growth was predicted both using the Paris law and the numerical model. Both predictions agree but only the numerical simulation is able to capture the crack retardation between load blocks.